Digital divide among elderly workers - a comparative study between Public and Private Sectors in Melaka / Hafisah Yaakob, Wan Hartini Wan Hassan and Faridah Pardi - Yaakob, Hafisah; Wan Hassan, Wan Hartini; Pardi, Faridah (2012)
Generally, this study explains the digital divide among elderly workers of ages 50 to 58 years in public and private sectors in the state of Melaka. The main purpose of the study is to reveal and distinguish the factors that contribute to digital divide among elderly workers of ages 50 to 58 years in public and private sectors. According to Ministry of Energy, Water and Communications digital divide is a reference that is given to the circumstances in which part of the community is not likely to ease of use of information communication technology (ICT) infrastructure caused by factors such as accessibility, capability, ability to use computer and lack of local content. The study focuses on factors that cause digital divide namely gender, age, ethnicity, education level, income level, and residential area. These factors are combined with job sector for any significant influence on level of digital divide. Indicators such as home personal computers ownership, Internet. subscription, Internet accessibility, computer usage, Internet usage, and computer knowledge and skills are used to measure the digital divide among elderly workers. The study is conducted to achieve three objectives; to examine the ability to use computer and digital divide among elderly between public and private sectors, to investigate distinction level of digital divide arising among elderly workers in public and private sectors and lastly to identify factors that cause digital divide among the elderly. Population of elderly workers of age 50 to 58 years are stratified into public and private sectors. From each of the sectors samples with the stated quota, that is, those workers of age between 50 and 58 years old are selected. From the results of the analysis obtained, there is a distinction that indicates emergence of digital divide among elderly workers between public and private sectors. Thus, as such, government should take more effective initiatives to address the digital divide issue among the elderly. Through these initiatives the digital gap among the elderly in public and private sectors can be bridged in helping the elderly to be more independent and competitive to face the challenging old days.